Breast Cancer: A Public Health Issue that is also Subject of Social Construction - Santamaría Ulloa, Carolina (2020)
Breast cancer claims thousands of lives all over the world every year. A historical perspective on the social construction of breast cancer policy is presented. This mini review examines breast cancer through a historical lens to provide evidence of how, through a dynamic process of social construction, different social actors constructed breast cancer into a public health issue that merits policymakers’ attention